Analysis of Current Assets and Its Impact on Liquidity Level at PT. PT. BUMI PUTERA Bandung - Jatnika Dwi Asri (JURISMA : Jurnal Riset Bisnis & Manajemen, 2014)
Â Â Â Â Â Â Â Â Â Â Â Â  Current assets is very important in company especially in its operational activities. Hopefully, with the sale of insurance product that are going to get the optimal benefit for the company in accordance with the desired target. Current assets rotate everyday and from rotation of the bias current assets are expected to repay short â€“ them debt will mature. Base on the above description, hence writer take tittle : â€œ Analysis of Current Assets and Its Impact on Liquidity Level at PT. Â PT. Bumi puteraÂ  Bandungâ€.Â Â Â Â Â Â Â Â Â Â Â  The aim of this paper are : (1) To know the development of current assets at Â PT. Bumi puteraÂ  Bandung, (2) To know the development of Liquidity at Â PT. Bumi puteraÂ  Bandung, (3) To determine the impact of current assets to liquidity at Â PT. Bumi puteraÂ  Bandung. The method used in the research is descriptive method with quantitative approach. Technique data collecting taken is bibliography study and field. While data analysis using correlation analysis, regression, determination, and test the â€œtâ€ in processed data by using SPSS 15.0 for Windows.Â Â Â Â Â Â Â Â Â Â Â  According to the study authors, show that there are influence between current Assets Turnover on the liquidity. There are levels of closeness of relationship (correlation) between these two variables, namely r = -0.967 with a positive correlation value. The point is that if the current assets turnover increases, liquidity increases, so does the opposite. While the value of determination coefficient of 93.51 % means that the current assets and its impact on liquidityÂ  Level at PT. Â PT. Bumi putera Bandungat 93.51 %, 6:49%, rest influence by other factors not examined in this study.Keywords : Current Assets, Liquidity